1992
DOI: 10.1111/j.1478-4408.1992.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carriers on the dyeing of Courtelle S

Abstract: The extent to which the uptake of CI Basic Blue 3 on Courtelle S tow was enhanced by three derivatives of benzyl alcohol was found to be proportional to the amount of each carrier adsorbed by the fibre, with maximum dye uptake coinciding with maximum uptake of carrier by the fibre. Although the maximum extent of uptake of each carrier corresponded approximately to the aqueous solubility of the carrier at the dyeing temperature (80°C) used, results from a previous study on the carrier action of benzyl alcohol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…), which are rapidly absorbed, have been used to accelerate the dyeing rate. But many effective carriers are also suspected environmental hazards 7–11. Thakore et al reported a dyeing process using ultrasonic to form and break small bubbles, making the dyeing better at low temperatures achieving levels comparable with dyeing at boiling using carriers 12–16.…”
Section: Introductionmentioning
confidence: 99%
“…), which are rapidly absorbed, have been used to accelerate the dyeing rate. But many effective carriers are also suspected environmental hazards 7–11. Thakore et al reported a dyeing process using ultrasonic to form and break small bubbles, making the dyeing better at low temperatures achieving levels comparable with dyeing at boiling using carriers 12–16.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the glass transition temperature (T g ) and dyeing transition temperature (T d ) of the fiber may be expected to be decreased during the carrier dyeing process, and the diffusion rate of dyes and the dye exhaustion to be increased [18,19]. Therefore, carriers could be used in the coloration of synthetic fiber, for example, for acrylic, PVC and polyphenylene sulfide fibers with cationic dyes [19][20][21][22][23], and for polyester and triacetate fibers with disperse dyes [24][25][26].…”
Section: June 2015mentioning
confidence: 97%